Selective harmonic measurement and compensation using smart inverters in a microgrid with distributed generation - Sousa, Tiago José Cunha (2018)
This paper presents a frequency domain selective harmonic measurement and compensation using smart inverters (SIs) applied to a microgrid with distributed generation. The compensation current is calculated by a main processing unit (MPU), which controls the compensation action of each distributed generation unit (DGU) connected to the microgrid. A single fast Fourier transform (FFT) is implemented to obtain the frequency spectra of the power grid voltages and the currents consumed by the connected loads. Based on the calculated compensation currents and the availability of the DGUs, the MPU establishes the harmonic orders that each DGU should compensate, aiming to equalize the rms current values among the different DGUs. The proposed approach intends to optimize the DGUs efficiency in the microgrid and, additionally, it allows the connection of the converters to the power grid without the need for a synchronization algorithm. A comprehensive description of the implemented FFT algorithm is performed and, finally, the operation of the proposed scheme is verified by simulation results.